National Open Data Cubes and Their Contribution to Country-Level Development Policies and Practices - Dhu, Trevor; Giuliani, Gregory; Juárez, Jimena; Kavvada, Argyro; Killough, Brian; Merodio, Paloma; Minchin, Stuart; Ramage, Steven (MDPI Data, 2019)
The emerging global trend of satellite operators producing analysis-ready data combined with open source tools for managing and exploiting these data are leading to more and more countries using Earth observation data to drive progress against key national and international development agendas. This paper provides examples from Australia, Mexico, Switzerland, and Tanzania on how the Open Data Cube technology has been combined with analysis-ready data to provide new insights and support better policy making across issues as diverse as water resource management through to urbanization and environmental–economic accounting.